Risk Factors for Rapidly Progressive Neurological Deterioration in Cervical Spondylotic Myelopathy. Issue 12 (15th June 2019) - Takasawa, Eiji; Sorimachi, Yasunori; Iizuka, Yoichi; Tsunoda, Daisuke; Mieda, Tokue; Iizuka, Haku; Chikuda, Hirotaka
Abstract : Study Design: A retrospective single-center study. Objective: This study sought to clarify the risk factors and to evaluate the surgical outcome in patients with rapidly progressive cervical spondylotic myelopathy (rp-CSM). Summary of Background Data: CSM is a degenerative spine disease presenting a slow development of myelopathy. Some patients, however, show rapidly progressive neurological deterioration (especially gait disturbances) without any trauma. At present, there is little information about this condition. Methods: We studied 71 consecutive CSM patients (52 men, 19 women) with a mean age of 67.1 years, and the follow-up period was 1 year. Patients were divided into two groups: rp-CSM and chronic-CSM (c-CSM) groups. The Japanese Orthopaedic Association score and various clinical differences, including age, sex, comorbidity, the waiting period from symptomatic onset to surgery, cervical range of motion, and intramedullary MR T2-hyperintensity were analyzed, and independent risk factors were determined using a logistic regression analysis. Results: Eighteen of 71 patients (25.4%) were diagnosed with rp-CSM. There were no significant differences between the two groups with regard to age, sex, or cervical range of motion. In the rp-CSM group, the preoperative upper/lower extremities and bladder functions were worse, and the waiting period for surgery was shorter (rp-CSM 1.2 mo, c-CSM 25.7 mo). Patients with rp-CSM had a history of cardiovascular event (CVE) (rp-CSM 44.4%, c-CSM 15.1%) and presented with MR T2-hyperintensity (rp-CSM 94.4%, c-CSM 58.5%), especially at the C4/5 disc level. Independent risk factors were a history of CVE (odds ratio = 4.7) and MR T2-hyperintensity (odds ratio  = 12.5). The rp-CSM group showed a better neurological recovery after decompression surgery (the Japanese Orthopaedic Association recovery rate: rp-CSM 64.5%, c-CSM 40.7%). Conclusion: A history of CVE and MR T2-hyperintensity were risk factors for rp-CSM. Despite rapid neurological deterioration, rp-CSM patients showed a good neurological recovery after surgery, and thus indicating that rp-CSM is a reversible condition. Level of Evidence: 4 Abstract : A history of cardiovascular event and intramedullary MR T2-hyperintensity were independent risk factors for rapidly progressive cervical spondylotic myelopathy (rp-CSM). Despite rapid neurological deterioration, rp-CSM patients showed a good neurological recovery after decompression surgery, and thus indicating that rp-CSM is a reversible condition.